2018
DOI: 10.21873/anticanres.12775
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Effect of Polaprezinc, a Zinc-L-carnosine, Against Chemotherapy-induced Oral Mucositis in Pediatric Patients Undergoing Autologous Stem Cell Transplantation

Abstract: PZ-AG was found to be highly effective in preventing oral mucositis in pediatric patients with hematological malignancies receiving high-dose chemotherapy followed by HSCT, as in adult patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 29 publications
0
26
0
2
Order By: Relevance
“…Following searches and removal of duplicates, 343 abstracts were screened and 66 full reports were assessed for eligibility (Figure 1). Excluded studies encompassed: reviews without original data, 31,32 single case reports, 33 data for degree and/or duration of IV opioid was not included, or the proportion of children requiring IV opioid analgesia was reported without specific details of the duration or dose, 34‐38 or opioid was administered by an alternative route (eg, intranasal 39 or topical 40 ; Figure 1). Seventeen articles (six RCTs, two prospective observational studies, three retrospective cohort studies, six retrospective case series) fulfilled inclusion criteria and reported the duration and/or dose of IV opioid in children with severe mucositis following chemotherapy for tumor management or HSCT 21‐23,41‐54 …”
Section: Resultsmentioning
confidence: 99%
“…Following searches and removal of duplicates, 343 abstracts were screened and 66 full reports were assessed for eligibility (Figure 1). Excluded studies encompassed: reviews without original data, 31,32 single case reports, 33 data for degree and/or duration of IV opioid was not included, or the proportion of children requiring IV opioid analgesia was reported without specific details of the duration or dose, 34‐38 or opioid was administered by an alternative route (eg, intranasal 39 or topical 40 ; Figure 1). Seventeen articles (six RCTs, two prospective observational studies, three retrospective cohort studies, six retrospective case series) fulfilled inclusion criteria and reported the duration and/or dose of IV opioid in children with severe mucositis following chemotherapy for tumor management or HSCT 21‐23,41‐54 …”
Section: Resultsmentioning
confidence: 99%
“…13 analgesics for oral pain. 8 The advantages of this treatment are: simplicity of execution, good tolerance of patients, absence of side effects or adverse reactions and high medical-social efficiency. 9 At present, the clinical evidence regarding the effect of Zinc is sparse.…”
Section: Introductionmentioning
confidence: 99%
“…We reported previously that oral ingestion of polaprezinc (PZ), a zinc‐L‐carnosine, preparation suspended in sodium alginate was highly effective for prevention of oral mucositis associated with radiotherapy in adult patients with head and neck cancer 21,22 as well as in adult 23 and pediatric 24 patients receiving high‐dose chemotherapy for HSCT. We found that a newly developed lozenge preparation containing PZ had efficacy almost comparable to that of the PZ suspension in sodium alginate 25 .…”
Section: Introductionmentioning
confidence: 99%
“…We found that a newly developed lozenge preparation containing PZ had efficacy almost comparable to that of the PZ suspension in sodium alginate 25 . However, the effects of PZ for patients receiving high‐dose chemotherapy for HSCT have been evaluated only in single‐institutional retrospective studies 23‐25 . To confirm the preventive effect of PZ against oral mucositis, we have carried out a multi‐institutional randomized controlled clinical study evaluating the efficacy of PZ lozenges for prevention of oral mucositis associated with chemotherapy in patients undergoing HSCT.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation